Electrical properties of MIS structures with silicon nanoclusters - Bunak, S.V.; Ilchenko, V.V.; Melnik, V.P.; Hatsevych, I.M.; Romanyuk, B.N.; Shkavro, A.G.; Tretyak, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The theoretical and experimental investigations of electrical properties of the
Al-SiO₂-( − ncsSi -SiO₂-Si structures grown using high temperature annealing SiOx, x < 2, have been carried out. It has been experimentally found that the Al-SiO₂-( − ncsSi )-SiO₂-Si structures with the tunnel dielectric layer revealed the effect of dynamic memory. Electric properties and parameters of the interface states located between − ncsSi and SiO₂ were studied in detail by measuring of current-voltage, capacitance-voltage, and thermally stimulated current characteristics.